Rare case of pulmonary fat embolism and acute respiratory distress syndrome after liposuction and fat grafting: a case report - Gai, Xiaoyan; Sun, Xiaoyan; Zhu, Xiang; Zhou, Qingtao; Sun, Yongchang (Frontiers in Medicine, 2023)
Background: Pulmonary fat embolism usually occurs after fracture, yet rarely observed after liposuction and fat grafting. Case presentation: We describe a 19-year-old female patient who presented with acute respiratory failure and diffuse pulmonary opacities on chest radiographic image shortly after liposuction and fat grafting. Bronchoalveolar lavage was performed and lipid content in alveolar cells contribute to the diagnosis of the fat embolism syndrome. The patient was successfully treated with noninvasive mechanical ventilation and a short course of glucocorticoids. Conclusions: Early recognition and appropriate treatment are very important to improve the outcome of pulmonary fat embolism. Considering that liposuction and fat grafting are increasingly common cosmetic surgeries, our aim is to raise awareness for this rare adverse event.